The possible association between epidemics of hand-foot-and-mouth disease and responsiveness to immunoglobulin therapy in Kawasaki disease - Shimizu, Daisuke; Hoshina, Takayuki; Kawamura, Masaru; Tomita, Yoshie; Hidaka, Yasufumi; Kojiro, Masumi; Muneuchi, Jun; Kamizono, Junji; Yamaguchi, Kenichiro; Fujino, Yoshihisa; Kusuhara, Koichi (Frontiers in Pediatrics, 2022)
Background: Enterovirus causing hand-foot-mouth disease (HFMD) has been reported to be associated with the development of Kawasaki disease (KD), whereas the involvement of enterovirus in the clinical course of KD is uncertain. The aim of this study is to investigate the association between the clinical course of KD and HFMD epidemics. Methods: This study included 108 patients who developed KD during HFMD epidemic seasons (July and August) from 2010 to 2014 and who were initially treated with high-dose intravenous immunoglobulin (IVIG). A mean of ≥5.0 HFMD patients reported weekly from each sentinel medical facility was considered to represent a large HFMD epidemic. We compared the clinical characteristics of KD patients in summers of years with and without large HFMD epidemics. Results: Large HFMD epidemics occurred in 2011 and 2013. The number of KD patients in summer was the highest in 2011. The proportion of patients with resistance to the IVIG therapy in summers of years with the large epidemics (14%) was significantly lower than that in summers of other years (31%, P = 0.030), whereas the proportion of patients with coronary artery abnormalities did not differ to a statistically significant extent. The development of KD during large HFMD epidemics was significantly associated with a lower risk of resistance to the IVIG therapy (incidence rate ratio 0.92, P = 0.049). Conclusion: Patients developing KD during large HFMD epidemic may have good responsiveness to IVIG. It is important to identify microbes from KD patients to predict responsiveness to IVIG therapy.